The Power of Law from modal ontology and the Communicational Theory of Law - Ortíz Díaz, Edimar Jhossed (Scientific journal of social studies, 2023)
This paper offers some theoretical foundations to the conception of law as constituted by language, from a weak or modal ontology and supported by the Communicational Theory of Law and literary hermeneutics, in opposition to the classical theories of law that conceive law as an entity whose existence is prior to language, from a strong ontological or merely ontological position.